Cytokine IL-5 and HGF: combined prediction of non-/low immune response to hepatitis B vaccination at birth in infants born to HBsAg-positive mothers - Ou, Guanyong; Qing, Ling; Zhang, Li; Yang, Yang; Ye, Guoguo; Peng, Ling; Li, Yanjie; Yang, Liuqing; Liu, Yingxia (Frontiers in Cellular and Infection Microbiology, 2024)
Background The immune response to hepatitis B vaccine may be influenced by numerous factors, and patients with non/low response re-exposed to hepatitis B virus remain susceptible. Thus, a better understanding of the underlying mechanisms of non/low immune response in infants born to Hepatitis B surface antigen (HBsAg)-positive mothers is essential. Methods 100 infants born to HBsAg-positive mothers from 2015 to 2020 were enrolled in the study, further divided into the non/low response group (n=13) and the moderate strong response group (n=87) based on the quantification of hepatitis B surface antibody at 12 months of age. The differential expression of 48 immune-related cytokines in the two groups was compared and analyzed in detail. The key cytokines were further identified and clinically predictive models were developed. Results We found that 13 cytokines were lowly expressed and one cytokine was highly expressed in the non/low response group, compared with the moderate strong response group at birth. In addition, 9 cytokines were lowly expressed and one cytokine was highly expressed in the non/low response group at 12 months of age. Furthermore, we found that IL-5 and HGF were promising predictors for predicting the immunization response to hepatitis B vaccine in infants, and the combination of the two cytokines showed the best predictive efficiency, with an area under the curve (AUC) value of 0.844. Conclusion The present study provides a theoretical basis on cytokines for developing and implementing effective immunotherapies against non/low immune response in infants born to HBsAg-positive mothers.